IMPROVING PATIENT SAFETY IN HEALTHCARE THROUGH EFFICIENT COMMUNICATION - Omar Jumaan Rashed, Hamad Abdulrahman Mobark Al Mohanna Al Dosari, ⁠Afrah Saud H. Almasoudi Alnawmasi, Abdullah Mofareh Ahmad Alkhaldi, Naif Daifallah Bakhit Alzahrany, Bishi Mansuor Algrni, Mousa Hassan Mousa Zeid, Turki Khalid M Alabdulrahman; Raed Fares Rwailli Al Anazi, Eman Fayez Mohammed Albishi, Kawthar Abdulazeem Aldarisi, Hessah Ahmed Mohammed Bin Jidah, Mousa Hasser Hmoud Masrahi, Majed Ghazi Alotaibi, Sarah Nasser Fahad Aldossari, ،sharifah Saleh Ahmed Alshahri (Chelonian Research Foundation, 2022)
The numerous interactions that healthcare professionals have on a daily basis require EFFECTIVE COMMUNICATION. To ensure that the right information is provided in a timely manner, staff members need to be proficient in both collaborative teamwork and efficient communication. Patient care is jeopardized in the absence of efficient communication. Breakdowns in communication have long been identified as the primary cause of most sentinel events examined since 1996 and as the primary cause of nearly all sentinel events reported to The Joint Commission's Sentinel Event Database. Power disputes, competing roles, unclear duties, and hierarchical inequalities can all result in poor communication, which jeopardizes patient safety and treatment quality. Keywords: nurse-physician communication, SBAR, STICC, patient safety.